Respuesta :
Answer:
Last option: [tex](x+1)^2+(y-1)^2=16[/tex]
Step-by-step explanation:
The missing figure is attached.
The center-radius form of the circle equation is:
[tex](x - h)^2 + (y-k)^2 = r^2[/tex]
Where the center of the circle is at the poitn [tex](h,k)[/tex] and "r" is the radius.
You can identify from the figure attached that the radius of the circle shown is 4 units.
Since the other circle has the same radius and its center is at the point [tex](-1, 1)[/tex]; you can identify that:
[tex]h=-1\\k=1\\r=4[/tex]
Therefore, substituting values into [tex](x - h)^2 + (y-k)^2 = r^2[/tex], you get that the equation of that circle is:
[tex](x - (-1))^2 + (y-1)^2 = 4^2\\\\(x+1)^2+(y-1)^2=16[/tex]
![Ver imagen luisejr77](https://us-static.z-dn.net/files/da2/7edab42b135362d0c0e1574f8c9c02d8.jpg)
Answer:
[tex]\displaystyle (x + 1)^2 + (y - 1)^2 = 16[/tex]
Step-by-step explanation:
According to the Center-Radius Formula, [tex]\displaystyle [X - H]^2 + [Y - K]^2 = R^2,[/tex][H, K] represents the centre of the circle, where the negative symbols give the OPPOSITE terms of what they really are, and the radius is ALWAYS squared. So, with the centre of [tex]\displaystyle [-1, 1][/tex]plus your radius of 4, you have this:
[tex](x + 1)^2 + (y - 1)^2 = 16[/tex]
I am joyous to assist you anytime.